2015
DOI: 10.1186/s12957-015-0539-0
|View full text |Cite
|
Sign up to set email alerts
|

Giant peritoneal loose body in the pelvic cavity confirmed by laparoscopic exploration: a case report and review of the literature

Abstract: A 51-year-old previously healthy male underwent a routine medical examination. Computed tomography and ultrasonography showed an oval-shaped mass that was about 50 × 40 mm in size in the left iliac fossa. Prior to surgery, the lesion was suspected to be a teratoma with core calcification or stromal tumor derived from the rectosigmoid colon. During the procedure, a yellow-white, egg-shaped mass was discovered that was completely free from the pelvic cavity in front of the rectum. The giant, peritoneal loose bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 22 publications
1
32
0
Order By: Relevance
“…A giant PLB in particular can cause acute, as well as chronic symptoms like mentioned in the introduction above [5] , [6] , [7] and reported in our own case. Nevertheless, it normally hasn’t got any clinical significance and is detected incidentally at radiological examination, laparoscopy/laparotomy or autopsy [8] .…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…A giant PLB in particular can cause acute, as well as chronic symptoms like mentioned in the introduction above [5] , [6] , [7] and reported in our own case. Nevertheless, it normally hasn’t got any clinical significance and is detected incidentally at radiological examination, laparoscopy/laparotomy or autopsy [8] .…”
Section: Discussionsupporting
confidence: 75%
“…Especially its “giant” form (gPLB) with a diameter >5 cm has rarely been described in the literature though this phenomenon has been known for over 300 years [2] , [3] , [4] . Although a gPLB can cause symptoms like abdominal and/or pelvic pain or discomfort with alternating localization [5] , intestinal obstruction [6] or urinary retention [7] , it is mostly detected incidentally at radiological examination, laparoscopy/laparotomy or autopsy [1] . Moreover, it is often misinterpreted as an intraabdominal tumor or foreign body, and overstated surgical procedures are carried out [8] .…”
Section: Introductionmentioning
confidence: 99%
“…They are usually located freely in the peritoneal cavity (1) and rarely cause symptoms. PLBs are usually 5-20 mm in diameter and are diagnosed via laparotomy or autopsy by accident (2). Matsubara et al (3) reviewed 20 reported PLB cases and determined that PLB is more common in males, with a male:female ratio of 17:3.…”
Section: Introductionmentioning
confidence: 99%
“…Giant PLBs measuring more than 5 cm are very rare, and only a few cases have been reported. A literature search found 20 cases of giant PLBs ( Table 1 ) [1] , [2] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] . Interestingly, as in our case, most giant PLBs occurred in men over age 50; three female cases were reported.…”
Section: Discussionmentioning
confidence: 99%